Application of VDVTA as Grounded Lossy Series and Parallel RL Circuit - Haseeb, Zainab; Prasad, Dinesh; Mainuddin; Akram, M. W. (Transactions on Engineering and Computing Sciences, 2025)
This paper presents two simple topologies of novel grounded lossy series and parallel RL circuit employing VDVTA. Inductor and resistor are simulated employing one VDVTA and one passive component. Both the proposed topologies for the immittance simulation have been realized using a simple circuit. There is little deviation in the values of theoretically calculated and practically simulated series and parallel RL circuit. To study the performance of the realized grounded lossy series and parallel RL circuit, a second order high pass filter has been constructed using one of the circuits. To verify the presented theoretical analysis, the PSPICE simulation results are given using CMOS technology.